Entrevistas: Camões 500 anos, com Annabela Rita e Maria Lúcia Dal Farra - Annabela Rita; Maria Lúcia Dal Farra; Jonas Jefferson de Souza Leite; Paulo Ricardo Braz (Revista Investigações)
Annabela Rita